Functionality, reliability and adaptability improvements to the OSSIM information security console (2009)
Security consoles are among the most widely deployed tools for information security management in today's organizations. This article summarizes the work of our research team, in order to incorporate several enhancements to the OSSIM information security console. Such enhancements include integration with physical security control devices, automatic creation of correlation directives for OSSIM's correlation engine, and a significant improvement in information capture reliability on high-traffic networks. © 2009 IEEE.